Stereotactic Body Radiotherapy for Oligometastatic Disease in Non-small Cell Lung Cancer - Wujanto, Caryn; Vellayappan, Balamurugan; Siva, Shankar; Louie, Alexander V.; Guckenberger, Matthias; Slotman, Ben J.; Onishi, Hiroshi; Nagata, Yasushi; Liu, Mitchell; Lo, Simon S. (Frontiers in Oncology, 2019)
Metastatic non-small cell lung cancer (NSCLC) is associated with a limited survival when treated with palliative intent platinum-based chemotherapy alone. Recent advances in imaging and therapeutic strategy have identified a subset of patients with limited metastases who may benefit from early local ablative therapy with either surgery or radiotherapy, in addition to standard treatment. Stereotactic body radiotherapy (SBRT) is increasingly used in the treatment of extra-cranial oligometastatic NSCLC (OM-NSCLC) due its non-invasive conduct and ability to deliver high doses. Clinical evidence supporting the use of SBRT in OM-NSCLC is emerging and consistently demonstrates significant benefit in local control and progression-free survival. Here, we discuss the definition of oligometastases (OM), review current available data on SBRT treatment in extra-cranial OM-NSCLC including evidence for site-specific SBRT in lung, liver, and adrenal metastases.